2020
DOI: 10.1007/s10826-020-01717-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Delivering Mindfulness-Based Programmes in Schools: A Qualitative Study

Abstract: There has been an increased interest in the delivery of Mindfulness-Based Programmes (MBPs) in schools yet little is known about how people who deliver MBPs in schools carry out and experience implementation. In this qualitative study, we aimed to examine the experiences of school staff who have a personal mindfulness practice, and who also deliver MBPs to their students. We recruited eight school staff (age range 34-64) who taught students mindfulness, and carried out semi-structured interviews focusing on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
3
11
0
Order By: Relevance
“…Research has shown that support from a mentor or peer can encourage the support of establishing MBI practices (Vitolo, 2018). Without peer support, educators are often reluctant to try, or sustain, new practices (Norton and Griffith, 2020).…”
Section: Lack Of Mentorship/peer Supportmentioning
confidence: 99%
See 3 more Smart Citations
“…Research has shown that support from a mentor or peer can encourage the support of establishing MBI practices (Vitolo, 2018). Without peer support, educators are often reluctant to try, or sustain, new practices (Norton and Griffith, 2020).…”
Section: Lack Of Mentorship/peer Supportmentioning
confidence: 99%
“…Districts are often unlikely to support MBI protocols because the proposed benefits are not immediately apparent or are unrelated to direct and measurable or short-return-on-investment outcomes (Klocko and Wells, 2015). There can be tension between the core principles of mindfulness approaches and "being expected to "sell" MBPs to schools" (Norton andGriffith, 2020, p. 2631).…”
Section: Culture Of Outcomes-based Productivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Mindfulness is another important issue that can be considered in relation to parents of children with special needs and the children themselves. One of the most characteristic definitions of mindfulness includes awareness arising from purposeful, instantaneous and non-biased attention (18)(19)(20)(21)(22)(23)(24). Petcharat and Liehr (20) associate mindful parenting with lower levels of stress, anxiety, and depression, and higher levels of psychological well-being in the parents of children with special needs.…”
Section: Extended Abstract Introductionmentioning
confidence: 99%